The Effect Of ESG Disclosure And Audit Quality On Company Value In The Basic Material Sector With Company Size As Moderator In 2021-2023 - Patricia Angelique; Grace Orlyn Sitompul; Judith Tagal Gallena Sinaga (Jurnal Ekonomi, 2024)
A company's worth is demonstrated by how well it performs and how well it accomplishes its goals. With a focus on basic materials businesses listed on the Indonesia Stock Exchange in 2021–2023, this study attempts to evaluate the effects of ESG disclosure and audit quality on company value while taking company size into account as a moderating factor. Based on a sample of 78 firm-year data, the study uses a quantitative methodology that includes multiple linear regression, moderation regression analysis, and descriptive statistics using SPSS 27. The results show that company size, audit quality, and ESG disclosure all have a major impact on company value. However, company size is found to weaken the effect of ESG disclosure and audit quality on company value. These results present a new challenge for future research to expand the scope of time and industries in order to better understand why company size does not moderate the relationship between ESG disclosure, audit quality, and company value.